Air quality management in Botswana - Akinola, M.O; Lekonpane, M; Dada, E.0 (Clean Air Journal, 2017)
This paper examines air pollution situation and the history of air quality management in Botswana. The current air quality management in Botswana is still largely underpinned by the Atmospheric Pollution Prevention Act of 1971, supplemented by the more recently enacted legislations such as the Environmental Impact Assessment (EIA) Act of 2010 and the Ambient Air Quality - Limits for Common Pollutants of 2012 published by the Botswana Bureau of Standards. Though commendable efforts have been made toward legislating against air and other forms of pollution, these have not yielded expected results in view of the prevailing levels of air pollutants like sulphur dioxide and fine particulate matters in the country’s atmospheric environment. Legislation as a sole measure may not be effective in tackling this challenge. Rather, government should also address some root-causes of the problem by making policies and programmes that will reduce unemployment and increase the earning capacity of citizenry. This will, among other things, effectively check poverty-induced biomass burning in the country. The paper looks at some other challenges of air pollution management and suggestions are made to tackle the identified problems.